Pyrolysis Modeling and Kinetic Study of Typical Insulation Materials for Building Exterior Envelopes - Youchao Zhang; Bo Wang; Li Xu; Zhiming Ma (Buildings)
Thermal insulation materials are important for building energy conservation, but the inherent combustibility of these materials increases the fire risk of building facades. To better understand the fire behaviors of these materials, the study of the kinetics of thermal insulation pyrolysis is particularly important because it is the initial step in ignition and combustion during fire. In this paper, the pyrolysis behavior of expanded polystyrene (EPS), a typical non-charring insulation polymer, has been investigated by thermogravimetric analysis at five different heating rates. The model-free kinetic analysis showed that the obtained average values for E and lnA were 151.23 kJ/mol and 21.29 ln/s, respectively. Model-fitting CR and masterplot methods indicated that f(α) = [2(1-α)[-ln(1-α)]]1/2 is considered the pyrolysis reaction mechanism of EPS degradation. Based on these results, the equation of the kinetic compensation effect was further developed as lnA = −3.1955 + 0.1736 Eα. Finally, the reaction model was reconstructed with the result of the expression f(α) = 3.95335α0.24174 (1-α) [-ln(1-α)]1.64712. In addition, PY-GC-MS experiments were conducted to analyze the composition of EPS pyrolysis volatiles. The results showed that the products were mainly compounds of benzene, naphthalene, and biphenyl. The analysis of EPS pyrolysis behavior and evolved gas provides numerical guidance for the future treatment and fire protection of insulation materials.